Upaya Diplomasi Budaya Indonesia Melalui Komite Seni Budaya Nusantara Pada Tahun 2017 - Murbawanto Putra, Arfrido Valentino; Kurnia Putri, Penny; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This research aims to describe the efforts of the Komite Seni Budaya Nusantara (KSBN), which is a non-government actor in promoting Indonesian culture at the international level. The Indonesian government requires the involvement of various parties in achieving its national interests. In terms of culture, the Government of Indonesia cooperates with KSBN as a partner to maintain, introduce and preserve Indonesian culture at the international level. This research analyzes the efforts of the KSBN using the concept of cultural diplomacy and NGO written using a qualitative-descriptive research method. In this research, KSBN involves various parties in the destination country in collaborating various cultural activities with Indonesian themes as an effort to maintain, introduce and preserve Indonesian culture at the international level. Activities carried out in the form of traditional dance performances, traditional music art performances, batik fashion shows, and exhibitions of Indonesian culture. Keywords : Cultural Diplomacy, Indonesia, KSBN, NGO